Identify Student Learning Styles in the New Normal Era : Study on Prospective Biology Teachers - Syamsu Rijal; Ahmad Yani; Siti Darwa Suryani; Ambo Upe (STAI Hubbulwathan Duri, 2023)
The diversity of students results in various learning styles and routines. This definitely calls for lecturers to be flexible with students' learning preferences, as preferences play a significant role in the learning process in the midst of a pandemic. This study intens to identify and analyze the learning preferences of prospective biology teachers at Puangrimaggalatung University's Faculty of Teacher Training and Education. Additionally, efficient teaching options in the new normal period The total sample was 102 students, using the total sampling technique. The research was carried out in the even semester of the 2021/2022 academic year. The instrument used is a learning style questionnaire. The data obtained are analyzed descriptively. The results showed that most learning styles of prospective Biology teachers at Puangrimaggalatung University, dominated by visual learning styles by 60%, kinesthetic by 19%, followed by auditory by 14% and the last one was a combination type by 7%. It can be concluded that the learning style of prospective biology teachers in the new normal era is a visual learning style, so it is necessary to develop learning tools or strategies that are able to accommodate student learning styles visually. The research sample is only present on one campus; additional sites and research samples may be included in larger studies. Given that the new normal needs learning new things, certain tactics are necessary. Therefore, further study is required to create learning models that can take into account different student learning preferences.